2015
DOI: 10.1158/1538-7445.sabcs14-s4-03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S4-03: Identification of a notch-driven breast cancer stem cell gene signature for anti-notch therapy in an ER+ presurgical window model

Abstract: Background: Resistance to endocrine therapy (ET; tamoxifen or aromatase inhibitors, AI) for ER+ breast cancer is a major cause of mortality and new treatment paradigms are needed. Cancer stem cells drive breast cancer growth and are resistant to standard therapy. Notch signaling aids survival of these resistant stem cells and is inhibited by gamma-secretase inhibitors (GSI). We showed combining GSI with ET in mice caused shrinkage of breast cancer tumors. A presurgical window biomarker modulation model was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Thus, there is a critical need for new therapeutic targets to reduce TICs in ER þ breast cancer to prevent resistance, tumor recurrence, tumor, and severe side effects. Through a biomarker clinical trial (ClinTrials.gov Identifier: NCT00756717), we identified DAXX as a novel gene whose transcript is upregulated after short exposure to a GSI during endocrine therapy preceding definitive surgery in a window biomarker trial (19). From publicly available expression data (kmplot.com), high DAXX RNA correlates with a longer RFS in women with ER þ breast cancer following endocrine therapy (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a critical need for new therapeutic targets to reduce TICs in ER þ breast cancer to prevent resistance, tumor recurrence, tumor, and severe side effects. Through a biomarker clinical trial (ClinTrials.gov Identifier: NCT00756717), we identified DAXX as a novel gene whose transcript is upregulated after short exposure to a GSI during endocrine therapy preceding definitive surgery in a window biomarker trial (19). From publicly available expression data (kmplot.com), high DAXX RNA correlates with a longer RFS in women with ER þ breast cancer following endocrine therapy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To identify new therapeutic NOTCH biomarkers and targets, Albain and colleagues completed a biomarker presurgical window trial (ClinTrials.gov Identifier: NCT00756717; ref. 19). Death domain-associated protein 6 (DAXX) was identified as a novel NOTCH target with potential clinical significance in ER þ breast cancer (manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…A promising approach is identification Notch downstream targets that are specifically expressed in breast tumors as biomarkers for prognosis or predictive markers of sensitivity to treatment. The identification of breast tumor specific Notch targets was conducted by using a pre-surgical window trial in women with early stage ER+ breast cancer [ 132 ]. In this trial, 22 women received neo-adjuvant letrozole (an aromatase inhibitor) or tamoxifen for 14 days, followed by addition of MK-0572 GSI for 11 days.…”
Section: Future Ideasmentioning
confidence: 99%
“…Furthermore, many novel Notch target transcripts were also regulated by the GSI. One of these was death-domain-associated protein 6 (DAXX), which was upregulated with GSI treatment [ 132 ]. Specifically, DAXX was identified to be a novel Notch1 target gene, and high expression of Notch1 repressed DAXX (unpublished data).…”
Section: Future Ideasmentioning
confidence: 99%
“…More recently, Gelsomino et al showed that mutations in the ESR1 gene encoding ERα associated with endocrine resistance promote a CSC phenotype through activation of Notch4 14 . A pilot clinical trial of short term GSI MK0752 in combination with letrozole or tamoxifen in early stage ERα+ breast cancer patients showed that this regimen was safe and produced molecular changes in tumors consistent with the inhibition of proliferation and "stemness" and the induction of apoptosis 15 . Based on these findings, we designed a phase 1b study of GSI-exemestane combination in the metastatic setting.…”
Section: Introductionmentioning
confidence: 99%